Barriers of Malaysian green hotels and resorts - Yusof, Zeenat Begam; Jamaludin, Mariam (Elsevier, 2014)
Recently there has been a tremendous effort in greening the tourism industry due to its negative environmental impacts. The efforts of greening the lodging industry in Malaysia is growing slowly due to several barriers. The aim of this study is to determine the barriers of green hotels and resorts in Malaysia. This study employed qualitative method using in depth interview of the case studies. Five case studies were chosen. The findings identified 12 barriers. The barriers are categorized under significant, less significant and non-significant barriers.